2002
DOI: 10.1046/j.1469-0705.2002.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Chorionicity determination in twin pregnancies: how accurate are we?

Abstract: Ultrasound assessment of chorionicity has a high sensitivity and specificity. This is further improved if the assessment is performed prior to 14 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 13 publications
1
50
2
7
Order By: Relevance
“…In the management of twin pregnancies, the first-trimester ultrasound examination is of critical importance as it distinguishes the high-risk MC pregnancy from the lower-risk DC pregnancy with high accuracy 2,3 . MC twins are considered to be at increased risk of adverse outcome compared to DC twins because of vascular anastomoses on the placenta [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…In the management of twin pregnancies, the first-trimester ultrasound examination is of critical importance as it distinguishes the high-risk MC pregnancy from the lower-risk DC pregnancy with high accuracy 2,3 . MC twins are considered to be at increased risk of adverse outcome compared to DC twins because of vascular anastomoses on the placenta [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound assessment of chorionicity is becoming popular and has been shown to have high sensitivity and specificity with increased accuracy if performed prior to 14 weeks' gestation (Scardo et al, 1995;Stenhouse et al, 2002). Stenhouse et al (2002) found that chorionicity can be accurately determined in over 95% of cases when antenatal transabdominal ultrasound is used. This level of accuracy, if routinely used, would allow not only improved clinical care but also aid in unravelling the mystery that still surrounds the exact influence that the chorion has on development.…”
Section: Figurementioning
confidence: 99%
“…In recent years it has been recognized that many of the adverse outcomes are related to monochorionic placentation 22 , and management of twin pregnancies is now firmly based around targeted ultrasound examinations for planning of further antenatal care and surveillance. A sonographic examination at 11-14 weeks of gestation allows accurate determination of chorionicity [30][31][32][33] , measurement of fetal nuchal translucency thickness for determination of risk for fetal trisomies 34,35 , and discordance for major fetal anomalies 36,37 . In monochorionic twin pregnancies, further examinations in early mid-trimester may allow detection of developing twinto-twin transfusion syndrome 38,39 .…”
mentioning
confidence: 99%